2018 IEEE Global Communications Conference (GLOBECOM) 2018
DOI: 10.1109/glocom.2018.8647490
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Energy Tradeoff Among Communication, Computation and Caching with QoI-Guarantee

Abstract: Energy efficiency is a fundamental requirement of modern data communication systems, and its importance is reflected in much recent work on performance analysis of system energy consumption.However, most works have only focused on communication and computation costs, but do not account for caching costs. Given the increasing interest in cache networks, this is a serious deficiency. In this paper, we consider the problem of energy consumption in data communication, compression and caching (C3) with a Quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Instead of solving the MINLP problem in (6) directly, we reformulate the MINLP (6) into a standard and equivalent form, which is needed by the V-SBB, by using an approach called Symbolic Reformulation [21] that is suitable for small problems. We omit the details here due to space constraint and refer readers to [22] for a detailed discussion.…”
Section: Variant Of Spatial Branch and Bound Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of solving the MINLP problem in (6) directly, we reformulate the MINLP (6) into a standard and equivalent form, which is needed by the V-SBB, by using an approach called Symbolic Reformulation [21] that is suitable for small problems. We omit the details here due to space constraint and refer readers to [22] for a detailed discussion.…”
Section: Variant Of Spatial Branch and Bound Algorithmmentioning
confidence: 99%
“…Here, we use the variable and the value selection rule specified in [21], under which the variable for the branching decision is the one that causes the maximal reduction in the feasibility gap between the solution of Step 2 and the exact problem. Then we partition R into R right and R left , and add them into L as well as delete R. Detailed discussion of the algorithm can be found in [22].…”
Section: A Variant Of Spatial Branch-and-bound Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent lack of user request arrival knowledge case is considered in [12] where caching, transcoding, and backhaul retrieving are jointly optimized. Another joint optimization research can be found in [16] which concentrates on the trade-offs between communication, computation and caching.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the above works do not take the routing policies into consideration [6], [8], [9], [12]- [15] or only adopt the shortest path [7], [10], [11], [16]. However, it is insufficient to only consider the shortest path routing especially when the network bandwidth is limited.…”
Section: Introductionmentioning
confidence: 99%